Wanprestasi yang Dilakukan oleh Keluarga Penerima Manfaat (KPM) Berdasarkan Permensos Nomor 1 Tahun 2018 di Desa Talang Belitar - Wulandari, Putri; Ratna, Laily; Hasanah, Uswatun (Al-DYAS, 2026)
The Family Hope Program (PKH) is a conditional social assistance program provided by the government to poor families to improve access to education, health, and social welfare. In its implementation, Beneficiary Families (KPM) not only have the right to receive assistance but are also obliged to fulfill commitments as regulated in Minister of Social Affairs Regulation Number 1 of 2018. However, field practices still show various forms of breach of obligation, such as absence from P2K2 meetings, failure to conduct health verification, and misuse of assistance funds. This study aims to identify the forms of breach of obligation by KPM, analyze the factors causing them, and evaluate the implementation of sanctions based on Minister of Social Affairs Regulation Number 1 of 2018. This study used a sociological juridical approach with an empirical legal method. Primary data were collected through observation and in-depth interviews with 57 KPM and social facilitators, while secondary data were obtained from regulations and the SIKS-NG system. The data were analyzed qualitatively using the Miles and Huberman model. The results showed that the main forms of breach of obligation included absence from P2K2 meetings, failure to conduct health verification at Posyandu, and misuse of assistance funds for online gambling. The factors causing breach of obligation included scheduling conflicts with the coffee harvest season, geographical constraints, and KPM’s low legal understanding. Sanctions were applied in accordance with procedures, ranging from verbal warnings to forced graduation. The conclusion of this study affirms that the effectiveness of implementing KPM obligations in PKH is strongly influenced by the suitability of the facilitation mechanism, socio-geographical conditions, and beneficiaries’ legal literacy. The implications of this study indicate the need for flexible facilitation schedules and the strengthening of digital and legal literacy among KPM so that PKH implementation becomes more accountable, well-targeted, and in accordance with regulatory provisions.